PENGEMBANGAN BAHAN AJAR BERBASIS E-BOOK UNTUK PEMBELAJARAN KIMIA SMA POKOK BAHASAN STRUKTUR ATOM - Betty Holiwarni; Johni Azmi (Jurnal Pendidikan Kimia Universitas Riau, 2017)
This research aims to develop e-book based teaching materials for senior high school chemistry lesson at the subject of atomic structure. The research method used is research development. The research used Four D Model as a guide which is implemented in four stages are define, design, develop, and disseminate. This research is only up to the development stage. Research data were collected through assessment form filled by 4 validators, 2 material professional and 2 media professional. The result showed of the assessment provided by validators each aspect considered was a very good category. The conclusion shows develop e-book based teaching materials for senior high school chemistry lesson at the subject of atomic structure have the valid criteria in terms of content and construction.